2021
DOI: 10.1021/acs.jafc.1c04199
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics and Nanoplastics: Emerging Contaminants in Food

Abstract: As current concerns about food safety issues around the world are still relatively serious, more and more food safety issues have become the focus of people's attention. What's more serious is that environmental pollution and changes in human lifestyles have also led to the emergence of contaminants in food, microplastics (MPs) and nanoplastics (NPs) being typical representatives. MPs and NPs (M/NPs) in food are gradually becoming recognized by regulatory authorities and the public. Most published reviews on M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(36 citation statements)
references
References 151 publications
(173 reference statements)
1
19
0
Order By: Relevance
“…Qingrun Liu et al (2021) have reported microplastics enter the soil ecosystem mostly through mulching and littering. After mulching, lm and other wastes decompose into microplastics/nanoplastics (M/NPs), which are subsequently transported to plants (fruits and vegetables) and animals (meat and milk) via sewage sludge, composting, and irrigation.…”
Section: Discussionmentioning
confidence: 99%
“…Qingrun Liu et al (2021) have reported microplastics enter the soil ecosystem mostly through mulching and littering. After mulching, lm and other wastes decompose into microplastics/nanoplastics (M/NPs), which are subsequently transported to plants (fruits and vegetables) and animals (meat and milk) via sewage sludge, composting, and irrigation.…”
Section: Discussionmentioning
confidence: 99%
“…While MPs have been detected in household dust, air, seafood (fish, molluscs, crustaceans), salt, bottled water, beer, milk, tap water, human faeces, and placenta (Mohamed Nor et al, [ 73 ]; Zhang et al, [ 126 ]; Ragusa et al [ 91 ]), the availability of data to obtain a comprehensive quantification of human exposure represented by these sources is currently limited due to a lack of data on food and other potentially significant exposure sources (Liu et al, [ 66 ]; Fadare et al, [ 39 ]; Dawson et al, [ 26 ]; Wright et al, [ 121 ]). Therefore, we used a default RSC of 20% consistent with the US EPA [ 110 ] guidance and tested the sensitivity of this assumption by varying the RSC from between 0.00001- 0.50, which we anticipate represents a reasonable range of extreme values aligned with scenarios whereby exposure to MPs in drinking water is either negligible or where it represents a potentially significant source of exposure, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…One of the sources of MP accumulation in the human body is the ingestion of food contaminated with MPs from the environment [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Another source is the release of large amounts of MPs from plastic packaging materials that come into direct contact with food, which has been confirmed by researchers.…”
Section: Introductionmentioning
confidence: 99%